Criminological theory: past to present : essential readings - Cullen, Francis T.; Agnew, Robert; Wilcox, Pamela (Oxford University Press, 2022)
"Criminological Theory: Past to Present by Francis T. Cullen, Roben Agnew, and Pamela Wilcox is a comprehensive and authoritative reader for upper-level undergraduate and graduate courses in criminological theory. An Introduction precedes each Part, as well as each individual reading, situating the book's selections within the historical development of criminological theory as a discipline"--